Study of First Principles of Mg-Si Binary Systems as Precipitates from T6 Heat Treatment of AL-MG-SI ALLOYS - Deni Haryadi; Haris Rudianto (INDONESIAN JOURNAL OF APPLIED PHYSICS, 2020)
One of the purposes adding the two main alloying elements Si and Mg in small quantities (≈ 1%) on Aluminum is to form strengthening precipitates in aluminium alloy, which typically contribute with a fivefold strength increase from pure aluminum. In the last decades, the investigation has begun to understand the structure and formation of the different phases during heat treatment. An important precipitate in Al-Mg-Si Alloy is β" and β.  when the Precipitate β is created after β" is that the strength suddenly drops and the alloy is said to be overaged. By means of a first-principles supercell approach and density functional theory calculations, this research studied precipitate energy and interface energy of precipitate β" and β. Results show that precipitate β have precipitate energy higher then β" but have interface energy lowers then β". And each low energy interface was found possesses interface with the Al matrix is fully incoherent. The final result of calculation and simulation values for the interfacial energies, precipitate energies and strain energies that can be used in future predictions of the characteristic precipitate.